Synthesis method of high-temperature electrolyte for predicting tolerable temperature based on cloud point characteristics

By introducing non-ionic surfactants with specific cloud points into the zinc ion battery electrolyte, the cloud point characteristics of the electrolyte are adjusted, and the problem of performance degradation of zinc ion battery performance in high-temperature environments is solved, and the high-temperature stability and cycling performance of the electrolyte are improved.

CN119764611APending Publication Date: 2025-04-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083150.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The performance of zinc ion batteries declines in high-temperature environments, and the stability of the electrolyte is affected, resulting in side reactions and capacity reduction, and even thermal runaway.

Method used

The cloud point characteristics of the electrolyte are adjusted to predict their high temperature resistance by introducing non-ionic surfactants with specific cloud points, such as fatty acid methyl ethoxylate (FMEE) or alcohol ethoxylate (AEO) into the electrolyte.

Benefits of technology

It significantly improves the stability of zinc ion batteries in high temperature environments, reduces the occurrence of side reactions, improves the circulation performance, and realizes the modification of the electrolyte through simple operation and low-cost methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764611A_ABST
    Figure CN119764611A_ABST
Patent Text Reader

Abstract

The invention relates to a method for synthesizing a high-temperature electrolyte for predicting tolerable temperature based on cloud point characteristics, which comprises the following steps: dissolving zinc salt in deionized water, and stirring for 20-30 minutes at room temperature to obtain a zinc salt aqueous solution with the concentration of 1-3 mol L1 after the zinc salt aqueous solution is uniform; and dissolving a nonionic surfactant with a specific cloud point in the zinc salt aqueous solution, mechanically stirring at room temperature, and uniformly stirring to obtain the high-temperature electrolyte for predicting the tolerable temperature based on the cloud point characteristics. The nonionic surfactant with the specific cloud point is fatty acid methyl ester ethoxylate or alcohol ethoxylate. The method is easy and convenient to operate, low in cost and capable of accurately predicting the high-temperature-resistant limit, the obtained electrolyte can remarkably improve the reliability and working efficiency of the zinc ion battery in the high-temperature environment, and a theoretical basis and a technical route are provided for development of the high-temperature battery technology in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a method for synthesizing a high-temperature electrolyte capable of predicting a tolerance temperature based on cloud point characteristics. Background Art

[0002] With the advancement of global energy transformation, zinc-ion batteries have gradually become an ideal choice for energy storage systems due to their high safety, environmental friendliness and low cost. However, the performance degradation of batteries in high temperature environments is still one of the main challenges restricting their widespread application. In particular, the stability of the electrolyte is easily affected under high temperature conditions, because high temperature environments will accelerate the decomposition of zinc-ion battery electrolytes, leading to side reactions and capacity reduction, and even thermal runaway. Therefore, designing an electrolyte with high thermal stability has become the key to improving the operating stability of zinc-ion batteries in high temperature environments.

[0003] Among the many strategies for optimizing electrolytes, the additive strategy has attracted much attention due to its simplicity, high efficiency and adjustable advantages. Among them, there are endless examples of non-ionic surfactants as additives. Non-ionic surfactants have an important characteristic-cloud point. Cloud point refers to the temperature at which the interaction force between molecules in the solution changes during heating, causing the solution to become turbid. By adjusting the type and concentration of non-ionic surfactants, the stability of the electrolyte at high temperatures can be precisely controlled. Previous studies have shown that the cloud point may be related to the high temperature resistance of the electrolyte, but the specific mechanism has not yet been fully clarified. Therefore, further research on the relationship between the cloud point characteristics and the high temperature performance of the electrolyte will provide more scientific guidance for electrolyte design. In addition to the cloud point characteristics, factors such as the molecular structure, polarity and interaction of non-ionic surfactants with solvents also play a key role in the high temperature resistance of the electrolyte.

[0004] In summary, it is particularly important to further improve the thermal stability and ionic conductivity of the electrolyte by optimizing the combination of these factors, thereby improving the performance of zinc-ion batteries at high temperatures. With in-depth research in this field, the design of high-temperature electrolytes for zinc-ion batteries will develop in a more precise and customized direction. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for synthesizing a high-temperature electrolyte which is simple to operate, low in cost and can accurately predict the high-temperature resistance limit and can predict the tolerance temperature based on the cloud point characteristics.

[0006] In order to solve the above problems, the present invention discloses a method for synthesizing a high-temperature electrolyte with a predicted tolerance temperature based on cloud point characteristics, characterized in that: the method comprises dissolving a zinc salt in deionized water, stirring at room temperature for 20 to 30 minutes, and obtaining a uniform solution with a concentration of 1 to 3 mol L −1a zinc salt aqueous solution; a nonionic surfactant with a specific cloud point is dissolved in the zinc salt aqueous solution, and mechanically stirred at room temperature. After stirring evenly, a high-temperature electrolyte with a predicted tolerance temperature based on the cloud point characteristics is obtained; the nonionic surfactant with a specific cloud point is fatty acid methyl ester ethoxylate (FattyMethyl Ester Ethoxylate, FMEE) or alcohol ethoxylates (Alcohol Ethoxylates, AEO).

[0007] The zinc salt is one of zinc trifluoromethanesulfonate (Zn(OTf)2), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc bromide (ZnBr2) or zinc nitrate (Zn(NO3)2).

[0008] The mass fraction of the nonionic surfactant with a specific cloud point in the electrolyte is 15% to 30%.

[0009] The alcohol ethoxylate (AEO) is one of the alcohol ethoxylates with ethoxylation degrees of 7, 9 and 25.

[0010] The mechanical stirring condition refers to a stirring speed of 300-500 r min −1 , stirring time is 12~24 h.

[0011] A high temperature electrolyte synthesized by the method as described above and having a predicted tolerance temperature based on cloud point characteristics.

[0012] The application of a high-temperature electrolyte whose tolerance temperature is predicted based on the turbidity point characteristics in zinc ion batteries as described above.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention introduces a nonionic surfactant with a specific turbidity point as an electrolyte additive. The additive acts as a water cluster regulator and reconstructs the hydrogen bond network through interaction with water molecules, thereby enhancing the stability of water molecules, reducing their activity, and inhibiting side reactions such as hydrogen evolution reaction. This effect effectively improves the surface stability and zinc deposition behavior of the zinc negative electrode, thereby improving the battery performance. It is worth noting that the turbidity point phenomenon is closely related to the role of nonionic surfactants in batteries. When the temperature rises, the intermolecular interaction force changes, and the solution changes from transparent to turbid. The increase in the turbidity point indicates that the intermolecular binding force increases, thereby improving the stability of the electrolyte at high temperature. Therefore, by regulating the type, concentration and molecular structure of the nonionic surfactant, the high temperature stability of the electrolyte can be accurately controlled, and its high temperature resistance can be predicted with the help of the turbidity point characteristics. The turbidity point characteristics of nonionic surfactants are not only an important indicator for predicting the high temperature adaptability of the electrolyte, but also play a positive role in the overall stability of the electrolyte. Through the "turbidity point effect", the additive system can significantly improve the stability of zinc ion batteries in high temperature environments, reduce the occurrence of side reactions, and improve cycle performance.

[0014] 2. The present invention can prepare a uniform modified electrolyte by mixing a nonionic surfactant with a zinc-based aqueous electrolyte in an appropriate proportion at room temperature. The operation is simple and efficient, and is convenient for large-scale production.

[0015] 3. The formulation and performance of the electrolyte of the present invention can be flexibly adjusted, and has low production cost and meets environmental protection standards, showing good practicality and commercial potential.

[0016] 4. The present invention can not only significantly improve the reliability and working efficiency of zinc ion batteries in high temperature environments, but also provide a theoretical basis and technical route for the development of future high temperature battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0018] Figure 1 The constant current charge and discharge test results of the electrolyte prepared in Example 1 of the present invention when applied to a zinc||zinc symmetrical battery at 60°C are shown.

[0019] Figure 2 The coulombic efficiency test result of the electrolyte prepared in Example 1 of the present invention when applied to a zinc||copper asymmetric battery at 60°C is shown.

[0020] Figure 3 Figure 3 is a graph showing the charge and discharge test results of the electrolyte prepared in Example 1 of the present invention when applied to a zinc||vanadium pentoxide full battery at 60°C.

[0021] Figure 4 This is a graph showing the charge and discharge test results of the electrolyte prepared in Example 1 of the present invention when applied to a zinc||vanadium pentoxide full battery in the range of 30°C to 110°C.

[0022] Figure 5 This is a comparison chart of liquid H NMR spectra of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.

[0023] Figure 6 Linear sweep cyclic voltammetry (LSV) diagrams of the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1.

[0024] Figure 7 The zinc||zinc symmetric battery assembled with the electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1 was charged at 60°C and 0.2 mA cm −2 , 0.2 mAh cm −2 Surface micromorphology of the zinc sheet after cycling for 50 h under the same conditions.

[0025] Figure 8 This is a graph showing the charge and discharge test results of the electrolyte prepared in Example 2 of the present invention when applied to a zinc||vanadium pentoxide full battery in the range of 30°C to 65°C.

[0026] Fig. 9 This is a graph showing the charge and discharge test results of the electrolyte prepared in Example 3 of the present invention when applied to a zinc||vanadium pentoxide full battery in the range of 30°C to 100°C.

[0027] Fig.10 This is a graph showing the charge and discharge test results of the electrolyte prepared in Example 4 of the present invention when applied to a zinc||vanadium pentoxide full battery in the range of 30°C to 110°C. DETAILED DESCRIPTION

[0028] A method for synthesizing a high-temperature electrolyte with a predicted tolerance temperature based on turbidity characteristics, wherein the method comprises dissolving a zinc salt in deionized water, stirring at room temperature for 20 to 30 minutes, and obtaining a solution with a concentration of 1 to 3 mol L −1 A zinc salt aqueous solution is prepared; a nonionic surfactant having a specific turbidity point is dissolved in the zinc salt aqueous solution, and mechanically stirred at room temperature at a stirring speed of 300-500 r min −1 , and the stirring time is 12~24 h. After stirring evenly, a high-temperature electrolyte with a predicted tolerance temperature based on the cloud point characteristics is obtained. The non-ionic surfactant with a specific cloud point is fatty acid methyl ester ethoxylate (FattyMethyl Ester Ethoxylate, FMEE) or alcohol ethoxylate (Alcohol Ethoxylates, AEO).

[0029] Wherein: the zinc salt is one of zinc trifluoromethanesulfonate (Zn(OTf)2), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc bromide (ZnBr2) or zinc nitrate (Zn(NO3)2).

[0030] The mass fraction of the nonionic surfactant with a specific cloud point in the electrolyte is 15%~30%, and the mass unit is kg g.

[0031] The alcohol ethoxylates (AEO) are preferably one of the alcohol ethoxylates with a degree of ethoxylation of 7, 9 and 25 (AEO-7, AEO-9 or AEO-25).

[0032] FMEE is usually formed by the reaction of fatty acid methyl ester and ethoxylate, and its structure is composed of alternating fatty acid methyl ester parts and ethoxy chains. The general structural formula is: RCOOCH2-(OCH2CH2) n , wherein R represents a fatty acid alkyl group and n is the number of ethoxy units.

[0033] AEO is formed by the reaction of alcohol and ethoxylate, and its structure is composed of alternating alcohol groups and ethoxy chains. The general structural formula is: R-(CH2CH2O) m −H, where R represents an alkyl group and m is the number of ethoxy units.

[0034] The cloud points of FMEE, AEO-7, AEO-9, and AEO-25 are ~95 °C, 54~62 °C, 77~82 °C, and 92~94 °C, respectively.

[0035] An application of a high-temperature electrolyte that predicts the temperature tolerance based on the cloud point characteristics in zinc-ion batteries. The battery consists of a positive electrode, a negative electrode, a separator and an electrolyte, which are assembled into a CR2032 button battery. The negative electrode is a zinc sheet, the separator is glass fiber, and the positive electrodes are zinc sheets, copper foils and vanadium pentoxide, respectively, which are assembled into zinc||zinc symmetric batteries, zinc||copper asymmetric batteries, and zinc||vanadium pentoxide full batteries. The specific process is as follows: Drop 100 μL of electrolyte on the glass fiber, assemble the battery in the order of negative electrode shell-negative electrode-electrolyte-diaphragm-electrolyte-positive electrode-gasket-shrapnel-positive electrode shell, and use a manual packaging machine for pressure packaging.

[0036] Example 1 Dissolve Zn(OTf)2 in deionized water to prepare 2 mol L −1Zn(OTf)2 aqueous solution; 20% FMEE liquid was added to the above solution, and mechanically stirred for 12 h at room temperature at a stirring speed of 300 r min −1 , that is, a high-temperature electrolyte whose tolerance temperature can be predicted based on the cloud point characteristics is obtained.

[0037] ⑴ The high-temperature electrolyte prepared based on the predicted tolerance temperature of the turbidity point characteristics was applied to the zinc||zinc symmetric battery. The assembled zinc||zinc symmetric battery was subjected to constant current charge and discharge tests at an appropriate current density and surface capacity. At 30 ℃, 1.0 mA cm −2 , 1.0 mAh cm −2 Under the same conditions, the Zn||Zn symmetric battery can stably cycle for more than 2000 h, and the polarization voltage has no obvious change, indicating that its interface stability to the zinc negative electrode is extremely high. −2 , 0.2 mAh cm −2 Under these conditions, the results are as follows Figure 1 As shown, the Zn||Zn symmetric battery can be stably cycled for more than 800 h.

[0038] (2) The high-temperature electrolyte prepared based on the predicted tolerance temperature of the turbidity point characteristics was applied to the zinc||copper asymmetric battery. The assembled zinc||copper asymmetric battery was tested for coulombic efficiency at an appropriate current density and surface capacity. At 30 °C, 2 mA cm −2 , 1.0 mAh cm −2 Under the same conditions, the Zn||Cu asymmetric battery can be stably cycled for more than 400 cycles, and the Coulombic efficiency remains at 99.4%, indicating that the reversibility of Zn deposition / stripping is still good. −2 , 0.2 mAh cm −2 Under these conditions, the results are as follows Figure 2 As shown, the Zn||Cu asymmetric battery can be stably cycled for more than 130 cycles.

[0039] ⑶ The prepared high-temperature electrolyte with predicted tolerance temperature based on the cloud point characteristics was applied to the zinc||vanadium pentoxide full battery. The assembled zinc||vanadium pentoxide full battery was discharged to 0.2 V at an appropriate current density and then charged to 1.6 V for long cycle charge and discharge tests.

[0040] At 30 °C, 5 A g −1 Under the same conditions, the full battery still has a capacity retention rate of 90.5% after more than 1000 cycles of stable cycling, and has excellent rate performance. −1 Under these conditions, the results are as follows Figure 3 As shown, after the full battery has been stably cycled for more than 600 cycles, there is still a capacity retention rate of 95.8%.

[0041] At 5 A g −1 The specific capacity change in the range of 30 ℃ to 110 ℃ was tested at a current density of 1.58 W. Figure 4 As shown. In the temperature range below the cloud point of the additive FMEE, the specific capacity gradually increases with increasing temperature. However, when the temperature approaches the cloud point of 95 °C, the specific capacity decays significantly and then quickly drops to 0. This result verifies the effectiveness of predicting the high temperature resistance of the electrolyte by the cloud point of the non-ionic surfactant additive.

[0042] Comparative Example 1 A simple preparation of aqueous zinc ion battery electrolyte: Zn(OTf)2 was dissolved in deionized water to prepare 2 mol L −1 The electrolyte is obtained by adding a Zn(OTf)2 aqueous solution. Compared with Example 1, the only difference is that FMEE is not added.

[0043] Figure 5 This is a comparison of the liquid NMR hydrogen spectra of the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1. It can be seen that after the addition of FMEE, the hydrogen peak in the spectrum moves to the low field, indicating that the introduction of FMEE forms new hydrogen bonds and destroys the original hydrogen bond network between water molecules.

[0044] Figure 6 The linear sweep cyclic voltammetry (LSV) diagrams of the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1 show that after adding FMEE, the electrochemical window is widened and the hydrogen evolution reaction is suppressed.

[0045] Figure 7 The zinc||zinc symmetric cells assembled with the electrolyte prepared in Example 1 and the electrolyte prepared in Comparative Example 1 were charged at 60 °C and 0.2 mA cm −2 , 0.2 mAh cm −2 Figure 2 shows the surface micromorphology of the zinc sheet after 50 h of cycling under the same conditions. After cycling with the modified electrolyte containing FMEE, the surface of the zinc sheet remained flat and smooth, with no dendrite growth; while the surface of the zinc sheet after cycling in the electrolyte described in Comparative Example 1 showed obvious depressions and zinc dendrites. This shows that the addition of FMEE effectively inhibits the formation of zinc dendrites and reduces the risk of dendrite penetration, thereby improving the stability of the zinc battery electrode interface.

[0046] Example 2 Dissolve Zn(OTf)2 in deionized water to prepare 2 mol L −1A 25% mass fraction of AEO-7 liquid was added to the above solution, and mechanical stirring was performed at room temperature for 12 h at a stirring speed of 300 r min −1 , that is, a high-temperature electrolyte whose tolerance temperature can be predicted based on the cloud point characteristics is obtained.

[0047] The high-temperature electrolyte prepared based on the cloud point characteristics predicts the temperature tolerance and is applied to the zinc||vanadium pentoxide full battery. According to the cloud point of AEO-7 in the range of 54~62 ℃, we speculate that the heat resistance limit of the battery should be within this range. The experimental results are shown in Figure 8 As shown, this conjecture is verified: before the cloud point, the capacity increases with increasing temperature; but once the temperature reaches the cloud point, the capacity drops sharply.

[0048] Example 3 Dissolve Zn(OTf)2 in deionized water to prepare 2 mol L −1 A 25% mass fraction of AEO-9 liquid was added to the above solution, and mechanical stirring was performed at room temperature for 12 h at a stirring speed of 300 r min −1 , that is, a high-temperature electrolyte whose tolerance temperature can be predicted based on the cloud point characteristics is obtained.

[0049] The high-temperature electrolyte prepared based on the cloud point characteristics predicts the temperature tolerance and is applied to the zinc||vanadium pentoxide full battery. According to the cloud point of AEO-9 in the range of 77~82 ℃, we speculate that the heat resistance limit of the battery should be within this range. The experimental results are shown in Fig. 9 As shown, this conjecture is verified: before the cloud point, the capacity increases with increasing temperature; but once the temperature reaches the cloud point, the capacity drops sharply to 0.

[0050] Example 4 Dissolve Zn(OTf)2 in deionized water to prepare 2 mol L −1 A 20% solid AEO-25 was added to the above solution and mechanically stirred for 12 h at room temperature at a speed of 300 rmin. −1 , that is, a high-temperature electrolyte whose tolerance temperature can be predicted based on the cloud point characteristics is obtained.

[0051] The high-temperature electrolyte prepared based on the cloud point characteristics predicts the temperature tolerance and is applied to the zinc||vanadium pentoxide full battery. According to the cloud point of AEO-25 in the range of 92~94 ℃, we speculate that the heat resistance limit of the battery should be within this range. The experimental results are as follows Fig.10 As shown, this conjecture is verified: before the cloud point, the capacity increases with increasing temperature; but once the temperature reaches the cloud point, the capacity drops sharply to 0.

Claims

1. A method for synthesizing a high-temperature electrolyte for predicting a tolerance temperature based on cloud point characteristics, characterized in that: This method involves dissolving zinc salt in deionized water and stirring at room temperature for 20 to 30 minutes to obtain a concentration of 1 to 3 mol L −1 a zinc salt aqueous solution; then dissolving a nonionic surfactant with a specific cloud point in the zinc salt aqueous solution, mechanically stirring at room temperature, and stirring evenly to obtain a high-temperature electrolyte whose tolerance temperature is predicted based on the cloud point characteristics; the nonionic surfactant with a specific cloud point is fatty acid methyl ester ethoxylate or alcohol ethoxylate.

2. The method for synthesizing a high-temperature electrolyte for predicting a tolerance temperature based on cloud point characteristics according to claim 1, characterized in that: The zinc salt is one of zinc trifluoromethanesulfonate, zinc chloride, zinc perchlorate, zinc bromide or zinc nitrate.

3. The method for synthesizing a high-temperature electrolyte for predicting a tolerance temperature based on cloud point characteristics according to claim 1, characterized in that: The mass fraction of the nonionic surfactant with a specific cloud point in the electrolyte is 15% to 30%.

4. The method for synthesizing a high-temperature electrolyte for predicting a tolerance temperature based on cloud point characteristics according to claim 1, characterized in that: The alcohol ethoxylate is one of alcohol ethoxylates having ethoxylation degrees of 7, 9 and 25.

5. The method for synthesizing a high-temperature electrolyte for predicting a tolerance temperature based on cloud point characteristics according to claim 1, characterized in that: The mechanical stirring condition refers to a stirring speed of 300-500 r min −1 , stirring time is 12~24 h.

6. A high temperature electrolyte synthesized by the method according to any one of claims 1 to 5 and having a predicted tolerance temperature based on cloud point characteristics.

7. Application of a high-temperature electrolyte with a predicted tolerance temperature based on cloud point characteristics as claimed in claim 6 in a zinc ion battery.